88.9k views
2 votes
If f(x)=3x and g(x)=2x what is (gof)(x)?

User Iank
by
5.2k points

2 Answers

3 votes

Answer:

Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3

Given f(x) and g(x), please find (fog)(X) and (gof)(x)

f(x) = 2x g(x) = x+3

print Print document PDF list Cite

Quick Answer

(fog)(x) = 2x + 6

(gof)(x) = 2x + 3

Expert Answers

HALA718 eNotes educator| CERTIFIED EDUCATOR

f(x) = 2x

g(x) = x + 3

First let us find (fog)(x)

(fog)(x) = f(g(x)

= f(x+3)

= 2(x+3)

= 2x + 6

==> (fog)(x) = 2x + 6

Now let us find (gof)(x):

(gof)(x) = g(f(x)

= g(2x)

= 2x + 3

==> (gof)(x) = 2x + 3

Explanation:


User Msanford
by
5.0k points
3 votes

Answer:

(gof)(x) = 6x

Explanation:

We have given two function and we have to find their function.

f(x) = 3x and g(x) = 2x

(gof)(x) = ?

The formula to find the composition of two function:

(gof)(x) = g(f(x))

Putting the values of given functions ,we get

(gof)(x) = g(3x)

(gof)(x) = 2(3x)

(gof)(x) = 6x which is the answer.

User Ashutosh Meher
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.